Service transition in the automotive industry. (1st January 2013) - Kessler, Tim; Stephan, Michael
Service transition has found its way into the automotive industry in recent years. However, the comparison with the mechanical engineering industry reveals that the service business of the automotive industry is still at the beginning. We raise the questions of why automotive companies increasingly diversify into services and if they have any advantages compared to other firms. To answer these questions we investigate the changing business environment in the automotive industry and take a closer look at general characteristics and advantages of services as compared with manufacturing activities. In the paper, we develop a process model of service diversification on the theoretical grounds of the resource-based view of the firm. The process model aims to explain the service transition process in the automotive industry. In the case study of BMW, a corporate strategic approach to becoming an integrated mobility provider is presented and analysed.